Peranan Orang Tua Dalam Pembinaan Ibadah Sholat Bagi Anak Di Era 4.0 - Julian, Muhammad; Arikarani, Yesi (STAI Bumi Silampari, 2024)
In the 4.0 era, human life is inseparable from gadgets. The impact of the development of the internet is very large, both positive and negative. In this day and age, many children are addicted to gadgets that have the potential to be very bad for their future, be it because of laziness to learn or poor education. This affects the role of parents in providing prayer habits for children. Who will be disturbed by the impact of technology if they are not accompanied by their parents? This research is discussed using a type of literature study approach by analyzing facts sourced from books, journals, and other news that are in accordance with the topic of discussion. The results of this study show that parents have an important role in fortifying children in the 4.0 era. Especially in increasing the spirit of learning and the desire to pray and carry out prayers. The importance of parental strategies includes being a good example, making a regular schedule, and teaching prayer in a fun way. So that the habit of prayer provides an important lesson that there are educational values, namely, the value of awareness, sense of responsibility, cleanliness, discipline, vigilance, prudence, and tawadhu'. Thus, the habit of prayer for children can be a valuable lesson in increasing one's faith and devotion.